Setting of Induction of Labour with Double-Balloon Catheter in Low-risk Pregnancies: Outpatient Versus Inpatient - Kehl, Sven; Gernhardt, Anne; Weiss, Christel; Schneider, Michael; Beckmann, Matthias; Pretscher, Jutta (Geburtshilfe und Frauenheilkunde, 2026)
Objectives Induction of labour is one of the most frequently performed obstetric procedures. This analysis aimed to assess maternal and neonatal outcomes after labour induction with a double-balloon catheter in an outpatient versus inpatient setting in low-risk term pregnancies. Methods In this retrospective cohort study, 1010 women with singleton, low-risk term pregnancies undergoing labour induction with a double-balloon catheter were analysed. Of these, 394 received outpatient and 616 inpatient cervical ripening. The primary outcome was the caesarean section rate; secondary outcomes included the induction-to-delivery interval, vaginal delivery within 24 hours and neonatal parameters. Results Delivery modes were comparable between groups (p=0.5524), but vaginal delivery within 24 hours occurred less frequently in the outpatient group (25.2% vs. 32.9%, p=0.0201). Neonatal outcomes were significantly better in the outpatient cohort, with lower rates of arterial umbilical cord pH <7.10 (2.0% vs. 5.5%, p=0.0067) and NICU admissions (6.9% vs. 15.1%, p<0.0001). Multiple logistic regression analysis identified nulliparity (OR = 10.545), maternal age (OR =1.076), and birth weight (OR =1.733) as significant predictors for caesarean section. Failure to achieve vaginal delivery within 24 hours was associated with higher BMI (OR =1.080), nulliparity (OR =4.191), and fetal macrosomia (OR =3.675), while labour onset by balloon catheter alone reduced this risk (OR =0.149). Outpatient induction was associated with a lower risk of arterial pH <7.10 (OR =0.352, p=0.0088). Conclusions Outpatient cervical ripening with a double-balloon catheter is a safe and effective alternative to inpatient induction in low-risk term pregnancies, with comparable delivery outcomes and potential neonatal benefits.
CRIS-Team Scopus Importer:2026-02-06
Keywords: balloon catheter; delivery; induction of labor; inpatient; outpatient; setting